Anti-inflammatory potential of casein enzymatic hydrolysate/gelatin methacryloyl scaffolds for vital pulp therapy - Paymanpour, Payam; Anselmi, Caroline [UNESP]; Cardoso, Lais M. [UNESP]; de Carvalho, Ana Beatriz Gomes [UNESP]; Soares, Igor Paulino Mendes [UNESP]; Hebling, Josimeri [UNESP]; Dal-Fabbro, Renan; Bottino, Marco C. (Springer Nature, 2024)
ObjectivesTo synthesize casein enzymatic hydrolysate (CEH)-laden gelatin methacryloyl (GelMA) fibrous scaffolds and evaluate the cytocompatibility and anti-inflammatory effects on dental pulp stem cells (DPSCs).Materials and methodsGelMA fibrous scaffolds with 10%, 20%, and 30% CEH (w/w) and without CEH (control) were obtained via electrospinning. Chemo-morphological, degradation, and mechanical analyses were conducted to evaluate the morphology and composition of the fibers, mass loss, and mechanical properties, respectively. Adhesion/spreading and viability of DPSCs seeded on the scaffolds were also assessed. The anti-inflammatory potential on DPSCs was tested after the chronic challenge of cells with lipopolysaccharides (LPS), followed by treatment with extracts obtained after immersing the scaffolds in α-MEM. The synthesis of the pro-inflammatory cytokines IL-6, IL-1α, and TNF-α was measured by ELISA. Data were analyzed by ANOVA/post-hoc tests (α = 5%).ResultsCEH-laden electrospun fibers had a larger diameter than pure GelMA (p ≤ 0.036). GelMA scaffolds laden with 20% and 30% CEH had a greater mass loss. Tensile strength was reduced for the 10% CEH fibers (p = 0.0052), whereas no difference was observed for the 20% and 30% fibers (p ≥ 0.6736) compared to the control. Young’s modulus decreased with CEH (p < 0.0001). Elongation at break increased for the 20% and 30% CEH scaffolds (p ≤ 0.0038). Over time, DPSCs viability increased across all groups, indicating cytocompatibility, with CEH-laden scaffolds exhibiting greater cell viability after seven days (p ≤ 0.0166). Also, 10% CEH-GelMA scaffolds decreased the IL-6, IL-1α, and TNF-α synthesis (p ≤ 0.035).ConclusionCEH-laden GelMA scaffolds facilitated both adhesion and proliferation of DPSCs, and 10% CEH provided anti-inflammatory potential after chronic LPS challenge.Clinical relevanceCEH incorporated in GelMA fibrous scaffolds demonstrated the potential to be used as a cytocompatible and anti-inflammatory biomaterial for vital pulp therapy.